Quantum-sized effects in oxidized silicon structures with surface II-VI nanocrystals - Karachevtseva, L.; Kuchmii, S.; Kolyadina, O.; Lytvynenko, O.; Matveeva, L.; Sapelnikova, O.; Smirnov, O.; Stroyuk, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The Si-SiO₂ interface in oxidized macroporous silicon structures with surface CdS and ZnO nanocrystals was investigated using the methods of electroreflectance and photoconductivity. The Franz-Keldysh effect, built-in electric field and surface quantization of charge carriers in the Si-SiO₂ region were revealed. The splitting of photoconductivity peaks was detected in the area of indirect band-to-band transition due to quantization of charge carriers in the surface silicon region, too. The latter data correlate with the results of the electroreflectance spectra measurements in the area of direct interband transition of oxidized macroporous silicon structures with surface CdS and ZnO nanocrystals.